Information Technologies in Architectural Pedagogy: from "Tool" to a "Comprehensive Educational Strategy" - Papamanolis, Antonios; Geropanta, Vasiliki (Emerging Trends in Education, 2021)
The introduction of Information Technologies (IT) in the field of Architecture has brought about revolutionary developments regarding pedagogical frameworks. This paper examines the influence of IT on educational strategies and presents an innovative educational approach for their use in teaching design. Furthermore, it argues that IT cannot be considered in isolation, as mere tools, but rather as part of a comprehensive educational strategy. Such a strategy should take into account the context, method and the subject of architectural pedagogy while answering questions regarding the time, form and content of design teaching. Firstly, the authors present salient historical points that identify the main circumstances under which IT were inserted in the field of architecture. Secondly, through a critical reflection on the latest research in the field, the authors aim to reveal the impact of introducing IT in architectural education. These observations are then juxtaposed with the challenges of innovative education approaches today. Finally, the authors develop an implementation strategy for renovating the architectural education framework where IT are involved, based on three axes: (a) the cultivation of craftsmanship, (b) the conceptualization of IT as a technique and, (c) the teaching of a computation logic in architecture.